Key Characteristics Of Rural Construction SMEs - Kamal, Ernawati Mustafa; Flanagan, Roger (Penerbit Universiti Sains Malaysia, 2014)
Small- and medium-sized enterprises (SMEs) are at the core of the Malaysian construction industry. They account for more than 90% of companies that accept construction work. Because the SMEs are the majority, their characteristics significantly affect the current practices in the industry. This paper sought to understand the key characteristics of Malaysian construction SMEs that operate in rural areas. The study was based on multiple case studies in five construction SMEs that operated in four different states in Malaysia. The case studies identified seven key characteristics of Malaysian rural construction SMEs: (1) motivation for survival, (2) no policy for the implementation of new technologies and training, (3) no preference on the types of construction work accepted, (4) dominated by a single owner; (5) small number of employees, (6) being affected by political scenarios and (7) different business approaches between Bumiputera and non-Bumiputera companies. This study provides the government agencies and the Construction Industry Development Board an indication of how they can assist SMEs improve their productivity and further improve the construction industry's performance by addressing the special characteristics of the SMEs. The study may also serve as a basis to understand SMEs in other countries because different cultures, traditions and problems that SMEs encountered are viewed differently in different countries.